2014
DOI: 10.1007/7854_2014_331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stress on Prefrontal Glutamatergic, Monoaminergic and Cannabinoid Systems

Abstract: Stress has been shown to have marked and divergent effects on learning and memory which involves specific brain regions, such as spatial and declarative memory involving the hippocampus, memory of emotional arousing experiences and fear involving the amygdala, and executive functions and fear extinction involving the prefrontal cortex or the PFC. Response to stress involves a coordinated activation of a constellation of physiological systems including the activation of the hypothalamic-pituitary-adrenal (HPA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 140 publications
2
3
0
Order By: Relevance
“…But it is possible that the promotion of the production and release of glucocorticoid by stress stimulation is involved. As mentioned above, glucocorticoid receptor stimulation in the prefrontal cortex increases the release of stress-related neuromodulator dopamine [28] in the prefrontal cortex, through the positive-feedback system to midbrain dopamine neurons [35]. The present results demonstrated that serum glucocorticoid was significantly increased 2 weeks after the isolated rearing, and this increase was boosted further after 4 to 6 weeks of stress delivery (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…But it is possible that the promotion of the production and release of glucocorticoid by stress stimulation is involved. As mentioned above, glucocorticoid receptor stimulation in the prefrontal cortex increases the release of stress-related neuromodulator dopamine [28] in the prefrontal cortex, through the positive-feedback system to midbrain dopamine neurons [35]. The present results demonstrated that serum glucocorticoid was significantly increased 2 weeks after the isolated rearing, and this increase was boosted further after 4 to 6 weeks of stress delivery (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
“…The physiological responses including the autonomic nervous system and the HPA axis and the behavioral reactions such as avoidance and escape, both caused by the exposure to stress, are essentially protective responses to the stress [21] [22]. Besides the peripheral effects such as increased blood sugar level, the release of glucocorticoid is known to release dopamine in the prefrontal cortex [28], another example for the adaptive response. However, it is also indicated that the brain system involved in stress reactions is formed dynamically depending on the developing process [29] [30], where stress given in the juvenile stage decreases hippocampal volume [31] and has impacts on emotions and cognitive functions after maturation [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that the promotion of the production and release of glucocorticoid by stress stimulation is involved. As noted, glucocorticoid receptor stimulation in the prefrontal cortex increases the release of the stress‐related neuromodulator dopamine in the prefrontal cortex, through the positive‐feedback system to midbrain dopamine neurons . In the present study, serum glucocorticoid was significantly increased 4 weeks after isolated rearing.…”
Section: Discussionsupporting
confidence: 70%
“…The physiological responses involving the autonomic nervous system and the HPA axis, and the behavioral reactions such as avoidance and escape, both caused by exposure to stress, are essentially protective responses to the stress . Besides the peripheral effects such as increased blood sugar, the release of glucocorticoid is known to release dopamine in the prefrontal cortex , another example of the adaptive response. The brain system involved in stress reactions, however, is formed dynamically depending on the development process , in which stress in the juvenile stage decreases hippocampal volume and has an effect on emotion and cognitive function after maturation .…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamines are known to control the initial response to stress, whereas glucocorticoids take a longer time to be secreted and have considerable long-lasting effects [ 14 ]. Acute stress induces specific patterns of neuronal activation within the brain and stimulates excess transmission in the dopaminergic projections in the prefrontal and anterior cingulate cortices [ 15 , 16 ]. Furthermore, acute stress induces the release of higher concentrations of glucocorticoids disrupting memory formation and impairing learning [ 17 19 ] because glucocorticoids can modulate these processes [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%